Nutritional Potential of Co-products of Two Species of Benin Cucurbits - YETE, PELAGIE; TOGBE, Finagnon Crépin Alexis; YOVO, Franck; WOTTO, D. Valentin; Sohounhloue, Dominique (My University, 2019)
In the perspective of sustainable development, which involves the use of all biomass, two oilseeds have been selected according to their potential interests: Citrullus lanatus and Lagenaria siceraria. The physico-chemical characterization (oil and extraction cake) has been done. Thus, for extracted oils, unsaturated fatty acids are in the majority with the predominance of oleic and linoleic acids (21.31 to 44.36% and 16.20 to 70.35% respectively). The study of unsaponifiable fractions revealed that: Citrullus lanatus oil contains 134 mg/100g sterols (including 78.60% β-sitosterol) and 83.9mg/100g tocopherols (including 73.7% α-tocopherol) and Lagenaria siceraria oil contains 124mg/100 sterols (including 58.14% β-sitosterol) and 76.4mg/100g tocopherols (including 66.9% α-tocopherol). Phospholipids (0.39 and 0.40% respectively for Lagenaria siceraria and Citrullus lanatus) were quantified on the basis of phosphorus content. This study shows the nutritional value of oils through their compositions in essential fatty acids, their richness in phytosterols and tocopherols on the one hand and the ways in which co-products resulting from the extraction of selected seeds on the other hand are valued. Research showing the influence of stabilizing agents on the quality and stability of oils should be carried out to make their use easier. Tests of the use of these oils in the fields of cosmetics, pharmaceuticals, paints and polymer synthesis industries could be carried out.
Keywords: Biomass; Citrullus Lanatus; Lagenaria Siceraria; Chemical Characterization